Closure of the Strait of Hormuz may trigger a bioinvasion super-spreader event - Mario N. Tamburri; James T. Carlton; April M. H. Blakeslee; Alejandro Bortolus; João Canning-Clode; Susana Carvalho; Andrew L. Chang; Ian C. Davidson; Sarah C. Donelan; Lisa A. Drake; Amy E. Fowler; Amy L. Freestone; et al. (Biological Invasions, 2026)

Mechanical site preparation treatment and species effects on carbon pools in 12-year-old American sycamore [Platanus occidentalis L.] and willow oak [Quercus phellos L.] riparian plantations, Virginia Piedmont, USA - Drake H. Lynn; W. Michael Aust; David R. Carter; P. Corey Green; John R. Seiler (New Forests, 2025)
Restoration of riparian forests can improve water quality and wildlife habitat and also sequester carbon. Unfortunately, failures of riparian restoration efforts are common due to planting mortality. Selection of well-suited species, dense planting and use of mechanical soil site preparations may potentially enhance wetland restoration plantings. Carbon valuation of forestland is increasing and additional research is needed to determine rates and pools of carbon accumulation in riparian areas. We evaluated the effects of four soil mechanical site preparation treatments (bedding, disking, pit and mounding, and ripping) and species selection (American sycamore [ Platanus occidentalis L.] and willow oak, [ Quercus phellos L.] on survival, growth and carbon storage across multiple pools: planted trees, herbaceous vegetation, fine roots, organic soil (litter) horizons, and the mineral soil. At 12 years, species selection was more important to carbon storage than site preparation. American sycamore was well-suited to the site and had better survival than willow oak (64% vs. 42% survival). American sycamore also stored more carbon across all site preparation methods than willow oak. Measured carbon storage averaged 74.8 Mg ha −1 for American sycamore treatments and 63.1 Mg ha −1 for willow oak treatments. The densely planted treatments established forests even in higher mortality willow oak plots. Results indicate that appropriate species planted at high densities may be used to enhance forest stand establishment and carbon storage in similar riparian restorations.

Triple oxygen isotopes in eggshell carbonate as a proxy of late Cenozoic CO2 and primary productivity - Vincent J. Hare; Drake A. Yarian; J. Tyler Faith; Chris Harris; Julia A. Lee-Thorp; Benjamin H. Passey; Kathryn G. Sokolowski; Loïc Ségalen (Geochimica et Cosmochimica Acta, 2025)

Effects of fruit novelty on feeding preference in four globally invasive frugivorous birds - Samuel B. Case; Kapua Kawelo; Josephine Hoh; Dylan O’hearn; Jinelle H. Sperry; Jeffrey T. Foster; Donald R. Drake; Jeferson Vizentin-Bugoni; J. Patrick Kelley; Corey E. Tarwater (Biological Invasions, 2024)

Reply to comment on: Carbonaceous matter in ∼3.5 Ga black bedded barite from the Dresser Formation (Pilbara Craton, Western Australia) – Insights into organic cycling on the juvenile earth - L. Weimann; M. Reinhardt; J.-P. Duda; H. Mißbach-Karmrodt; H. Drake; J. Schönig; J. Holburg; L.B. Andreas; J. Reitner; M.J. Whitehouse; V. Thiel (Precambrian Research, 2024)

A Review on the State of the Art in Frugivory and Seed Dispersal on Islands and the Implications of Global Change - Manuel Nogales; Kim R. McConkey; Tomás A. Carlo; Debra M. Wotton; Peter J. Bellingham; Anna Traveset; Aarón González-Castro; Ruben Heleno; Kenta Watanabe; Haruko Ando; Haldre Rogers; Julia H. Heinen; et al. (The Botanical Review, 2024)
We provide an overview of the current state of knowledge of island frugivory and seed dispersal and identify knowledge gaps that are important for fundamental research on—and applied conservation of—island ecosystems. We conducted a systematic literature search of frugivory and seed dispersal on islands, omitting large, continental islands. This revealed a total of 448 studies, most (75%) published during the last two decades, especially after 2010. Nearly 65% of them were focused on eight archipelagos. There is a paucity of studies in Pacific archipelagos near Asia and Australia, and in the Indian Ocean. Data on island frugivory and seed dispersal are diverse but highly uneven in geographic and conceptual coverage. Despite their limited biodiversity, islands are essential reservoirs of endemic plants and animals and their interactions. Due to the simplicity of insular ecosystems, we can assess the importance of seed dispersal theory and mechanisms at species and community levels. These include the ecological and biogeographical meaning and prevalence of non-standard mechanisms of seed dispersal on islands; the seed dispersal effectiveness and the relative roles of different frugivore guilds (birds and reptiles being the most important); and patterns of community organization and their drivers as revealed by interaction networks. Island systems are characterized by the extinction of many natives and endemics, and high rates of species introductions. Therefore, understanding how these losses and additions alter seed dispersal processes has been a prevailing goal of island studies and an essential foundation for the effective restoration and conservation of islands.

Corrigendum: Turbulent diapycnal fluxes as a pilot Essential Ocean Variable - Arnaud Le Boyer; Nicole Couto; Matthew H. Alford; Henri F. Drake; Cynthia E. Bluteau; Kenneth G. Hughes; Alberto C. Naveira Garabato; Aurélie J. Moulin; Thomas Peacock; Elizabeth C. Fine; Ali Mashayek; Laura Cimoli; et al. (Frontiers in Marine Science, 2024)

Carbonaceous matter in ∼ 3.5 Ga black bedded barite from the Dresser Formation (Pilbara Craton, Western Australia) – Insights into organic cycling on the juvenile Earth - L. Weimann; M. Reinhardt; J.-P. Duda; H. Mißbach-Karmrodt; H. Drake; J. Schönig; J. Holburg; L.B. Andreas; J. Reitner; M.J. Whitehouse; V. Thiel (Precambrian Research, 2024)

Aspects of the biological carbon cycle in a ca. 3.42-billion-year-old marine ecosystem - M. Reinhardt; V. Thiel; J.-P. Duda; A. Hofmann; D. Bajnai; W. Goetz; A. Pack; J. Reitner; M. Schanofski; J. Schönig; M.J. Whitehouse; H. Drake (Precambrian Research, 2024)

DNA metabarcoding reveals diet composition of invasive rats and mice in Hawaiian forests - Sara M. E. Gabrielson; Rebecca L. Mau; Erika Dittmar; J. Patrick Kelley; Corey E. Tarwater; Donald R. Drake; Jinelle H. Sperry; Jeffrey T. Foster (Biological Invasions, 2024)

Turbulent diapycnal fluxes as a pilot Essential Ocean Variable - Arnaud Le Boyer; Nicole Couto; Matthew H. Alford; Henri F. Drake; Cynthia E. Bluteau; Kenneth G. Hughes; Alberto C. Naveira Garabato; Aurélie J. Moulin; Thomas Peacock; Elizabeth C. Fine; Ali Mashayek; Laura Cimoli; et al. (Frontiers in Marine Science, 2023)
We contend that ocean turbulent fluxes should be included in the list of Essential Ocean Variables (EOVs) created by the Global Ocean Observing System. This list aims to identify variables that are essential to observe to inform policy and maintain a healthy and resilient ocean. Diapycnal turbulent fluxes quantify the rates of exchange of tracers (such as temperature, salinity, density or nutrients, all of which are already EOVs) across a density layer. Measuring them is necessary to close the tracer concentration budgets of these quantities. Measuring turbulent fluxes of buoyancy ( J b ), heat ( J q ), salinity ( J S ) or any other tracer requires either synchronous microscale (a few centimeters) measurements of both the vector velocity and the scalar (e.g., temperature) to produce time series of the highly correlated perturbations of the two variables, or microscale measurements of turbulent dissipation rates of kinetic energy ( ϵ ) and of thermal/salinity/tracer variance ( χ ), from which fluxes can be derived. Unlike isopycnal turbulent fluxes, which are dominated by the mesoscale (tens of kilometers), microscale diapycnal fluxes cannot be derived as the product of existing EOVs, but rather require observations at the appropriate scales. The instrumentation, standardization of measurement practices, and data coordination of turbulence observations have advanced greatly in the past decade and are becoming increasingly robust. With more routine measurements, we can begin to unravel the relationships between physical mixing processes and ecosystem health. In addition to laying out the scientific relevance of the turbulent diapycnal fluxes, this review also compiles the current developments steering the community toward such routine measurements, strengthening the case for registering the turbulent diapycnal fluxes as an pilot Essential Ocean Variable.

From raw data to publication: Introducing data editing at Ecology Letters - Peter H. Thrall; Jonathan Chase; John Drake; Nathalie Espuno; Stephane Hello; Vanessa Ezenwa; Barbara Han; Akira Mori; Helene Muller‐Landau (Ecology Letters, 2023)

Hydrogeochemical and isotopic signatures elucidate deep subsurface hypersaline brine formation through radiolysis driven water-rock interaction - D.M. Nisson; T.L. Kieft; H. Drake; O. Warr; B. Sherwood Lollar; H. Ogasawara; S.M. Perl; B.M. Friefeld; J. Castillo; M.J. Whitehouse; E. Kooijman; T.C. Onstott (Geochimica et Cosmochimica Acta, 2023)

Introduced galliforms as seed predators and dispersers in Hawaiian forests - Samuel B. Case; Katherine Postelli; Donald R. Drake; Jeferson Vizentin-Bugoni; Jeffrey T. Foster; Jinelle H. Sperry; J. Patrick Kelley; Corey E. Tarwater (Biological Invasions, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Fruit and seed traits of native and invasive plant species in Hawai‘i: implications for seed dispersal by non-native birds - Jinelle H. Sperry; Dylan O’Hearn; Donald R. Drake; Amy M. Hruska; Samuel B. Case; Jeferson Vizentin-Bugoni; Clint Arnett; Tim Chambers; Corey E. Tarwater (Biological Invasions, 2021)

Direct effects influence larval salamander size and density more than indirect effects - Thomas L. Anderson; Brittany H. Ousterhout; Freya E. Rowland; Dana L. Drake; Jacob J. Burkhart; William E. Peterman (Oecologia, 2021)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Fusarium solani haplotype 12‐b and aortic and branchial arteritis in Hippocampus erectus Perry - Tori Brown; Zach Millar; Drake Evans; Phuc H. Pham; Veronique LePage; John S. Lumsden (Journal of Fish Diseases, 2020)

The association of metformin use with prostate cancer aggressiveness among Black Americans and White Americans in a population-based study - Saira Khan; Jianwen Cai; Matthew E. Nielsen; Melissa A. Troester; James L. Mohler; Elizabeth T. H. Fontham; Laura Farnan; Bettina F. Drake; Andrew F. Olshan; Jeannette T. Bensen (Cancer Causes & Control, 2018)

Quantifying the extent of niche areas in the global fleet of commercial ships: the potential for “super-hot spots” of biofouling - Cameron S. Moser; Timothy P. Wier; Matthew R. First; Jonathan F. Grant; Scott C. Riley; Stephanie H. Robbins-Wamsley; Mario N. Tamburri; Gregory M. Ruiz; A. Whitman Miller; Lisa A. Drake (Biological Invasions, 2017)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Towards minimizing transport of aquatic nuisance species in ballast water: Do organisms in different size classes respond uniformly to biocidal treatment? - Matthew R. First; Stephanie H. Robbins-Wamsley; Scott C. Riley; Lisa A. Drake (Biological Invasions, 2016)

Automated analysis of temperature variance to determine inundation state of wetlands - Thomas L. Anderson; Jennifer L. Heemeyer; William E. Peterman; Michael J. Everson; Brittany H. Ousterhout; Dana L. Drake; Raymond D. Semlitsch (Wetlands Ecology and Management, 2015)

Erratum to: Clinical Immunogenicity of rHuPH20, a Hyaluronidase Enabling Subcutaneous Drug Administration - Sanna Rosengren; Samuel S. Dychter; Marie A. Printz; Lei Huang; Richard I. Schiff; Hans-Peter Schwarz; John K. McVey; Fred H. Drake; Dan C. Maneval; Don A. Kennard; Gregory I. Frost; Barry J. Sugarman; et al. (The AAPS Journal, 2015)

Clinical Immunogenicity of rHuPH20, a Hyaluronidase Enabling Subcutaneous Drug Administration - Sanna Rosengren; Samuel S. Dychter; Marie A. Printz; Lei Huang; Richard I. Schiff; Hans-Peter Schwarz; John K. McVey; Fred H. Drake; Dan C. Maneval; Don A. Kennard; Gregory I. Frost; Barry J. Sugarman; et al. (The AAPS Journal, 2015)

Differential dispersal shapes population structure and patterns of genetic differentiation in two sympatric pond breeding salamanders - William E. Peterman; Thomas L. Anderson; Brittany H. Ousterhout; Dana L. Drake; Raymond D. Semlitsch; Lori S. Eggert (Conservation Genetics, 2015)

3D imaging provides a high-resolution, volumetric approach for analyzing biofouling - Matthew R. First; Steven A. Policastro; Matthew J. Strom; Scott C. Riley; Stephanie H. Robbins-Wamsley; Lisa A. Drake (Biofouling, 2014)

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Transformation of Althaea officinalis L. by Agrobacterium rhizogenes for the production of transgenic roots expressing the anti-HIV microbicide cyanovirin-N - Pascal M. W. Drake; Luisa de Moraes Madeira; Tim H. Szeto; Julian K-C. Ma (Transgenic Research, 2013)

Climate‐associated population declines reverse recovery and threaten future of an iconic high‐elevation plant - Paul D. Krushelnycky; Lloyd L. Loope; Thomas W. Giambelluca; Forest Starr; Kim Starr; Donald R. Drake; Andrew D. Taylor; Robert H. Robichaux (Global Change Biology, 2013)
Although climate change is predicted to place mountain‐top and other narrowly endemic species at severe risk of extinction, the ecological processes involved in such extinctions are still poorly resolved. In addition, much of this biodiversity loss will likely go unobserved, and therefore largely unappreciated. The H aleakalā silversword is restricted to a single volcano summit in H awai‘i, but is a highly charismatic giant rosette plant that is viewed by 1–2 million visitors annually. We link detailed local climate data to a lengthy demographic record, and combine both with a population‐wide assessment of recent plant mortality and recruitment, to show that after decades of strong recovery following successful management, this iconic species has entered a period of substantial climate‐associated decline. Mortality has been highest at the lower end of the distributional range, where most silverswords occur, and the strong association of annual population growth rates with patterns of precipitation suggests an increasing frequency of lethal water stress. Local climate data confirm trends toward warmer and drier conditions on the mountain, and signify a bleak outlook for silverswords if these trends continue. The silversword example foreshadows trouble for diversity in other biological hotspots, and illustrates how even well‐protected and relatively abundant species may succumb to climate‐induced stresses.

Nonhuman primate models of social behavior and cocaine abuse - Michael A. Nader; Paul W. Czoty; Susan H. Nader; Drake Morgan (Psychopharmacology, 2012)

Recombinant human hyaluronidase PH20 (rHuPH20) facilitates subcutaneous infusions of large volumes of immunoglobulin in a swine model - David W. Kang; Laurence Jadin; Tara Nekoroski; Fred H. Drake; Monica L. Zepeda (Drug Delivery and Translational Research, 2012)

Early life sun exposure, vitamin D-related gene variants, and risk of non-Hodgkin lymphoma - Jennifer L. Kelly; Matthew T. Drake; Zachary S. Fredericksen; Yan W. Asmann; Mark Liebow; Tait D. Shanafelt; Andrew L. Feldman; Stephen M. Ansell; William R. Macon; Megan M. Herr; Alice H. Wang; Grzegorz S. Nowakowski; et al. (Cancer Causes & Control, 2012)

Impact of a reduced winter snowpack on litter arthropod abundance and diversity in a northern hardwood forest ecosystem - Pamela H. Templer; Andrew F. Schiller; Nathan W. Fuller; Anne M. Socci; John L. Campbell; John E. Drake; Thomas H. Kunz (Biology and Fertility of Soils, 2012)

Movement and persistence by Ross’s Geese (Chen rossii) in Canada’s arctic - Ray T. Alisauskas; Kiel L. Drake; Jason H. Caswell; Dana K. Kellett (Journal of Ornithology, 2012)

Nitrogen source and p CO 2 synergistically affect carbon allocation, growth and morphology of the coccolithophore E miliania huxleyi : potential implications of ocean acidification for the carbon cycle - Stephane C. Lefebvre; Ina Benner; Jonathon H. Stillman; Alexander E. Parker; Michelle K. Drake; Pascale E. Rossignol; Kristine M. Okimura; Tomoko Komada; Edward J. Carpenter (Global Change Biology, 2012)
Coccolithophores are unicellular phytoplankton that produce calcium carbonate coccoliths as an exoskeleton. E miliania huxleyi , the most abundant coccolithophore in the world's ocean, plays a major role in the global carbon cycle by regulating the exchange of CO 2 across the ocean‐atmosphere interface through photosynthesis and calcium carbonate precipitation. As CO 2 concentration is rising in the atmosphere, the ocean is acidifying and ammonium ( NH 4 + ) concentration of future ocean water is expected to rise. The latter is attributed to increasing anthropogenic nitrogen ( N ) deposition, increasing rates of cyanobacterial N 2 fixation due to warmer and more stratified oceans, and decreased rates of nitrification due to ocean acidification. Thus, future global climate change will cause oceanic phytoplankton to experience changes in multiple environmental parameters including CO 2 , pH , temperature and nitrogen source. This study reports on the combined effect of elevated p CO 2 and increased NH 4 + to nitrate ( NO 3 − ) ratio ( NH 4 + / NO 3 − ) on E . huxleyi, maintained in continuous cultures for more than 200 generations under two p CO 2 levels and two different N sources. Herein, we show that NH 4 + assimilation under N ‐replete conditions depresses calcification at both low and high p CO 2 , alters coccolith morphology, and increases primary production. We observed that N source and p CO 2 synergistically drive growth rates, cell size, and the ratio of inorganic to organic carbon. These responses to N source suggest that, compared to increasing CO 2 alone, a greater disruption of the organic carbon pump could be expected in response to the combined effect of increased NH 4 + / NO 3 − ratio and CO 2 level in the future acidified ocean. Additional experiments conducted under lower nutrient conditions are needed prior to extrapolating our findings to the global oceans. Nonetheless, our results emphasize the need to assess combined effects of multiple environmental parameters on phytoplankton biology to develop accurate predictions of phytoplankton responses to ocean acidification.

A numerical study of inferred rockfish ( Sebastes spp.) larval dispersal along the central California coast - CHRISTINE H. PETERSEN; PATRICK T. DRAKE; CHRISTOPHER A. EDWARDS; STEPHEN RALSTON (Fisheries Oceanography, 2010)
Successful recruitment of marine fishes depends on survival during early life‐history stages, which is influenced by oceanic advection due to its impact on coastal trophodynamics and transport processes. Here we evaluate the influence of ocean circulation on the dispersal of rockfish ( Sebastes spp.) larvae along the central California coast using an implementation of the Regional Ocean Modeling System, driven at the surface by output from the Coupled Ocean Atmosphere Mesoscale Prediction System. Thousands of floats simulating rockfish larval propagules, constrained to follow fixed depths, were released over a broad coastal area at 2‐day intervals, and transported by simulated ocean currents at depths of 1, 7, 20, 40, and 70 m. Trajectory statistics are averaged across the 4‐yr period from January 2000 through December 2003 to reveal mean trajectory direction, net displacement, fractional cross‐shore loss, and duration of retention for different seasons. On average, near‐surface propagules originating nearshore are transported offshore during the upwelling season, whereas deeper propagules move alongshore to the north. This vertical shear vanishes during winter, with most floats moving alongshore to the north, regardless of depth. After 35 days in the water column, typical transport distances were ∼50 km for floats remaining nearshore and ∼150 km for floats over the midshelf and slope. Implications for performance of marine reserves for rockfish conservation are discussed. Our results also provide evidence for a strong semiannual pattern of coastal retention rates, with high export of near‐surface drifters during the upwelling season. In contrast, high rates of shelf retention occurred for releases at 20 m and deeper during summer, and at all depths during winter.

Forest carbon use efficiency: is respiration a constant fraction of gross primary production? - EVAN H. DeLUCIA; JOHN E. DRAKE; RICHARD B. THOMAS; MIQUEL GONZALEZ‐MELER (Global Change Biology, 2007)
Carbon‐use efficiency (CUE), the ratio of net primary production (NPP) to gross primary production (GPP), describes the capacity of forests to transfer carbon (C) from the atmosphere to terrestrial biomass. It is widely assumed in many landscape‐scale carbon‐cycling models that CUE for forests is a constant value of ∼0.5. To achieve a constant CUE, tree respiration must be a constant fraction of canopy photosynthesis. We conducted a literature survey to test the hypothesis that CUE is constant and universal among forest ecosystems. Of the 60 data points obtained from 26 papers published since 1975, more than half reported values of GPP that were not estimated independently from NPP; values of CUE calculated from independent estimates of GPP were greater than those calculated from estimates of GPP derived from NPP. The slope of the relationship between NPP and GPP for all forests was 0.53, but values of CUE varied from 0.23 to 0.83 for different forest types. CUE decreased with increasing age, and a substantial portion of the variation among forest types was caused by differences in stand age. When corrected for age the mean value of CUE was greatest for temperate deciduous forests and lowest for boreal forests. CUE also increased as the ratio of leaf mass‐to‐total mass increased. Contrary to the assumption of constancy, substantial variation in CUE has been reported in the literature. It may be inappropriate to assume that respiration is a constant fraction of GPP as adhering to this assumption may contribute to incorrect estimates of C cycles. A 20% error in current estimates of CUE used in landscape models (i.e. ranging from 0.4 to 0.6) could misrepresent an amount of C equal to total anthropogenic emissions of CO 2 when scaled to the terrestrial biosphere.

The use of reference strand‐mediated conformational analysis for the study of cheetah ( Acinonyx jubatus ) feline leucocyte antigen class II DRB polymorphisms - G. J. C. Drake; L. J. Kennedy; H. K. Auty; R. Ryvar; W. E. R. Ollier; A. C. Kitchener; A. R. Freeman; A. D. Radford (Molecular Ecology, 2004)
There is now considerable evidence to suggest the cheetah ( Acinonyx jubatus ) has limited genetic diversity. However, the extent of this and its significance to the fitness of the cheetah population, both in the wild and captivity, is the subject of some debate. This reflects the difficulty associated with establishing a direct link between low variability at biologically significant loci and deleterious aspects of phenotype in this, and other, species. Attempts to study one such region, the feline leucocyte antigen (FLA), are hampered by a general reliance on cloning and sequencing which is expensive, labour‐intensive, subject to PCR artefact and always likely to underestimate true variability. In this study we have applied reference strand‐mediated conformational analysis (RSCA) to determine the FLA–DRB phenotypes of 25 cheetahs. This technique was rapid, repeatable and less prone to polymerase chain reaction (PCR)‐induced sequence artefacts associated with cloning. Individual cheetahs were shown to have up to three FLA–DRB genes. A total of five alleles were identified (DRB*ha14–17 and DRB*gd01) distributed among four genotypes. Fifteen cheetahs were DRB*ha14/ha15/ha16/ha17, three were DRB*ha15/ha16/ha17, six were DRB*ha14/ha16/ha17 and one was DRB*ha14/ha15/ha16/ha17/gd01. Sequence analysis of DRB*gd01 suggested it was a recombinant of DRB*ha16 and DRB*ha17. Generation of new alleles is difficult to document, and the clear demonstration of such an event is unusual. This study confirms further the limited genetic variability of the cheetah at a biologically significant region. RSCA will facilitate large‐scale studies that will be needed to correlate genetic diversity at such loci with population fitness in the cheetah and other species.

Direct and indirect effects of elevated CO 2 on transpiration from Quercus myrtifolia in a scrub‐oak ecosystem - J.‐H. Li; W. A. Dugas; G. J. Hymus; D. P. Johnson; C. R. Hinkle; B. G. Drake; B. A. Hungate (Global Change Biology, 2003)
Elevated atmospheric carbon dioxide (C a ) usually reduces stomatal conductance, but the effects on plant transpiration in the field are not well understood. Using constant‐power sap flow gauges, we measured transpiration from Quercus myrtifolia Willd., the dominant species of the Florida scrub‐oak ecosystem, which had been exposed in situ to elevated C a (350 µmol mol − 1 above ambient) in open‐top chambers since May 1996. Elevated C a reduced average transpiration per unit leaf area by 37%, 48% and 49% in March, May and October 2000, respectively. Temporarily reversing the C a treatments showed that at least part of the reduction in transpiration was an immediate, reversible response to elevated C a . However, there was also an apparent indirect effect of C a on transpiration: when transpiration in all plants was measured under common C a , transpiration in elevated C a ‐grown plants was lower than that in plants grown in normal ambient C a . Results from measurements of stomatal conductance (g s ), leaf area index (LAI), canopy light interception and correlation between light and g s indicated that the direct, reversible C a effect on transpiration was due to changes in g s caused by C a , and the indirect effect was caused mainly by greater self‐shading resulting from enhanced LAI, not from stomatal acclimation. By reducing light penetration through the canopy, the enhanced self‐shading at elevated C a decreased stomatal conductance and transpiration of leaves at the middle and bottom of canopy. This self‐shading mechanism is likely to be important in ecosystems where LAI increases in response to elevated C a .

Cocaine- and food-maintained responding under a multiple schedule in rhesus monkeys: environmental context and the effects of a dopamine antagonist - Michael A. Nader; Rachna S. Sinnott; Robert H. Mach; Drake Morgan (Psychopharmacology, 2002)

The biology of insularity: an introduction - Donald R. Drake; Christa P. H. Mulder; David R. Towns; Charles H. Daugherty (Journal of Biogeography, 2002)
Insular environments, ranging from oceanic islands to fragments of once‐contiguous natural systems, have long been used by biologists to test basic principles of ecology, evolution and biogeography. More recently, insular environments have figured prominently in conservation ecology, where the aim has usually been to conserve species or assemblages unique to isolated habitats. Improving the level of communication among the evolutionary biologists, theoretical ecologists and conservation biologists who study insular biotas will work to the benefit of all. This volume was inspired by a recent conference on the ecology of insular biotas, in which participants from a wide range of disciplines came together to compare ecological processes across a variety of taxonomic groups inhabiting a wide range of isolated environments. In this introduction, we point out the themes underlying these very diverse contributions. First we elaborate on the value of islands for elucidating processes underlying ecosystem functioning, population dynamics of reintroduced species, and restoration of disturbed habitats, and emphasize those areas where the use of islands could be expanded. The second section focuses on the link between ecology and evolutionary processes in insular systems and includes examples from oceanic islands, naturally patchy habitats and recently fragmented habitats. The third section illustrates some of the ways that invasive alien species on oceanic islands affect plant–animal mutualisms, particularly seed dispersal and pollination. The final section, on consequences of habitat fragmentation, focuses mainly on studies that describe the consequences that fragmentation has for plants and animals as they are forced into artificially insular environments. We close with a study that points out the differences among types of insular systems and identifies gaps in our knowledge of insular biotas, particularly the importance of explicitly incorporating patch type, age and patch–matrix contrasts in research. Finally, we recommend a greater emphasis on linking ecological theory and applied research, and improving communication between those who ask basic ecological questions and those who use insular systems for conservation.

Leaf senescence of Quercus myrtifolia as affected by long‐term CO 2 enrichment in its native environment - J. ‐H. Li; P. Dijkstra; G. J. Hymus; R. M. Wheeler; W. C. Piastuch; C. R. Hinkle; B. G. Drake (Global Change Biology, 2000)
Summary The long‐term effects of elevated (ambient plus 350 μmol mol −1 ) atmospheric CO 2 concentration (C a ) on the leaf senescence of Quercus myrtifolia Willd was studied in a scrub‐oak community during the transition from autumn (December 1997) to spring (April 1998). Plants were grown in large open‐top chambers at the Smithsonian CO 2 Research Site, Merritt Island Wildlife Refuge, Cape Canaveral, Florida. Chlorophyll (a + b) concentration, Rubisco activity and N concentration decreased by 75%, 82%, and 52%, respectively, from December (1997) to April (1998) in the leaves grown at ambient C a . In contrast, the leaves of plants grown at elevated C a showed no significant decrease in chlorophyll (a + b) concentration or Rubisco activity, and only a 25% reduction in nitrogen. These results indicate that leaf senescence was delayed during this period at elevated C a . Delayed leaf senescence in elevated C a had important consequences for leaf photosynthesis. In elevated C a the net photosynthetic rate of leaves that flushed in Spring 1997 (last year's leaves) and were 13 months old was not different from fully‐expanded leaves that flushed in 1998, and were approximately 1 month old (current year's leaves). In ambient C a the net photosynthetic rate of last year's leaves was 54% lower than for current year's leaves. When leaves were fully senesced, nitrogen concentration decreased to about 40% of the concentration in non‐senesced leaves, in both CO 2 treatments. In April, net photosynthesis was 97% greater in leaves grown in elevated C a than in those grown at ambient. During the period when elevated C a delayed leaf senescence, more leaves operating at higher photosynthetic rate would allow the ecosystem dominated by Q. myrtifolia to gain more carbon at elevated C a than at ambient C a .

Metabolism of aromatic aldehydes as cosubstrates by the acetogen Clostridium formicoaceticum - Claudia Frank; U. Schwarz; Carola Matthies; H. L. Drake (Archives of Microbiology, 1998)